EFFECTIVENESS OF VITAMIN A IN THE PREVENTION OF COMPLICATIONS OF PREMATURITY : SYSTEMATIC REVIEW - Stevenie, (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2023)
The phrase "vitamin A" refers to a group of chemicals that are fat-soluble and include retinol, retinyl palmitate, and beta-carotene. Vitamin A is a generic name. The numerous metabolites of this compound are required for normal vision, cellular development, epithelial barrier function, and immunological function. In the eyes, periocular glands, respiratory system, gastrointestinal tract, and genitourinary tract, a lack of vitamin A leads to the development of stratified, keratinizing epithelium, which eventually replaces normal epithelium. An excessive amount of vitamin A has immediate as well as long-term negative consequences on one's health. A disorder known as bronchopulmonary dysplasia is something that frequently occurs as a direct result of premature birth. BPD is a disorder that affects around twenty percent of babies who have a very low birth weight and more than fifty percent of infants who have an extremely low birth weight. BPD is a condition that affects approximately twenty percent of newborns who have a very low birth weight. It has the potential to cause a significant amount of morbidity. According to the findings of this research, the impact of vitamin A supplementation on the risk of BPD may be more pronounced in infants who had a lower birth weight than those who had a greater birth weight when compared with the general population. It was associated with a decreased incidence of type 1 retinopathy of prematurity, and it may also have a positive impact on reducing the prevalence of bronchopulmonary dysplasia. It was discovered that supplementing with vitamin A might reduce the severity of VA deficits in extremely preterm babies.